The PROPHECI trial: a phase II, double-blind, placebo-controlled, randomized clinical trial for the treatment of pseudoxanthoma elasticum with oral pyrophosphate - Laetitia Clotaire; Isabelle Rubera; Christophe Duranton; Jocelyn Gal; Emmanuel Chamorey; Hélène Humeau; Samir Yamani; Christine Chiaverini; Serge Willoteaux; Bernard Padovani; Laurie Mourozeau; Adam Mainguy; et al. (Trials)
Abstract Background /aims. Pseudoxanthoma Elasticum (PXE, OMIM 264800) is an autosomal, recessive, metabolic disorder characterized by progressive ectopic calcification in the skin, the vasculature and Bruch’s membrane. Variants in the ABCC6 gene are associated with low plasma pyrophosphate (PPi) concentration. There is currently no reference treatment for this chronic debilitating disease. Methods PROPHECI (PyROphosPHate supplementation to fight ECtopIc calcification in PseudoXanthoma Elasticum) is the first phase II, randomized, double-blind, placebo-controlled clinical trial (NTC 04868578) to evaluate the efficacy and safety of a daily oral PPi salt supplementation to attenuate and/or stabilize the progression of ectopic calcification in PXE patients. The primary endpoint is the change in arterial calcification volume quantified by non-contrast CT scan between baseline and 12 months of treatment. Secondary endpoints include the safety and efficacy of daily oral PPi administration on ocular and skin lesions and the evaluation of patients’ quality of life. Discussion The PROPHECI trial aims to provide safety and efficacy data on the use of daily oral PPi to reduce or stabilize ectopic calcification in PXE. It also aims to validate the best markers to include in the design of future trials for the treatment of PXE and other parent diseases. Trial registration Trial registration number: NCT 04868578. References can be found on the ClinicalTrials.gov website: https://clinicaltrials.gov/study/NCT04868578?cond=Pseudoxanthoma%20Elasticum&intr=pyrophosphate&rank=2